Business-to-consumer (B2C) e-commerce success of fashion industry in Malaysia - Siti Nur Afiqah, Mohammad Tarmizi (2021)
In Malaysia, the growing popularity and development of business-to-consumer (B2C) e-commerce have necessitated competition between existing B2C e-commerce. This growth has opened an opportunity for many fashion businesses to leverage this platform. To access and measure how this platform can contribute to their business success, this study has used the DeLone, and McLean IS success model 2003 in identifying the related factors. Five dimensions were examined: system quality, information quality, service quality, user satisfaction, and net benefit. Therefore, this study aims to analyze the influence of these variables to determine the major contributing factor on the B2C e-commerce fashion websites success in the fashion industry. Primarily, this study draws a quantitative method that was conducted through a survey questionnaire with 272 respondents who have experience purchasing apparel from B2C e-commerce websites. Statistical Package for Social Science (SPSS) was used to analyze the collected data, and Pearson correlation and multiple regression analysis were conducted to prove the hypothesis. These findings revealed that system quality, service quality, information quality, and user satisfaction significantly influence the net benefits of e-commerce fashion to achieve a successful online business. This study has provided theoretical implications to validate the DeLone & McLean Information Systems Success Model and practical implications.